1988
DOI: 10.1172/jci113828
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of hepatic function in liver cirrhosis in the rat. Multivariate analysis.

Abstract: We investigated the determinants of hepatic clearance functions in a rat model of liver cirrhosis induced by phenobarbital/CCI4. Aminopyrine N-demethylation (ABT), galactose elimination (GBT), and serum bile acids (SBA) were determined in vivo. The livers were then characterized hemodynamically: intrahepatic shunting (IHS) was determined by microspheres and sinusoidal capillarization by measuring the extravascular albumin space (EVA) by a multiple indicator dilution technique. The intrinsic clearance was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
0
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 47 publications
6
59
0
2
Order By: Relevance
“…In the normal liver, this diffusion is instantaneous because the endothelium contains fenestrae of 50 -200 nm in diameter and has no basement membrane. Since the apparent molecular diameter for Gd-DOTA is 0.9 nm (38), the assumption that the extraction fraction (E) of the contrast agent equals 1.0 is reasonable in the normal liver and hepatic perfusion (F) can therefore be considered to equal k 1 . In addition to k 1 , the outflow rate constant k 2 was also estimated and with both rate constants the distribution volume of the contrast agent and its mean transit time could be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the normal liver, this diffusion is instantaneous because the endothelium contains fenestrae of 50 -200 nm in diameter and has no basement membrane. Since the apparent molecular diameter for Gd-DOTA is 0.9 nm (38), the assumption that the extraction fraction (E) of the contrast agent equals 1.0 is reasonable in the normal liver and hepatic perfusion (F) can therefore be considered to equal k 1 . In addition to k 1 , the outflow rate constant k 2 was also estimated and with both rate constants the distribution volume of the contrast agent and its mean transit time could be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Liver hemodynamics is a main determinant of hepatic function (1,2). In patients with liver cirrhosis, modifications of hepatic perfusion contribute to the deterioration of hepatic function by decreasing blood-hepatocyte exchanges (3).…”
mentioning
confidence: 99%
“…The Goresky model has previously been used to estimate the mean transit time of vascular and extravascular references in the fibrotic rat liver. 5,6,30 In general, various space-distributed models using vascular and extravascular references as a basis for drug disposition in perfused livers should be comparable although not mathematically identical. The significantly larger liver/body weight ratio for CCl 4 -treated (phenobarbital/CCl 4 treatment), CCl 4 -control (phenobarbital treatment), and alcohol-treated rats compared with alcohol-control (normal) rats (Table 1) is likely to be treatment induced.…”
Section: Discussionmentioning
confidence: 99%
“…The second model exposes rats to CCl 4 vapors concomitantly to phenobarbital and results in cirrhosis. 14,15,32 To quantify the effect of biliary fibrosis on the expression of IP 3 R isoforms, we used four different methods, one at the protein level and three at the mRNA level. They all found that 28 days after bile duct ligation, IP 3 R isoform 2 was less abundant, IP 3 R isoform 1 more abundant, and isoform 3 was several-fold more expressed ( Table 1).…”
Section: Discussionmentioning
confidence: 99%